An eco-friendly method for analysis of sulfonamides in water samples using a multi-pumping system - Catelani, Tiago Augusto [UNESP]; Castoldi, Karine [UNESP]; Tóth, Ildikó Vargáné; Santos, João Luís Machado; Da Costa Lima, José Luís Fontes; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (Canadian Science Publishing, 2016)
A new methodology for determination of sulfonamides (sulfaquinoxaline, sulfathiazole, and sulfadimethoxine) in water samples was developed by coupling an automated multi-pumping flow system (MPFS) with a liquid waveguide capillary cell (LWCC; pathlength, 100 cm) and a spectrophotometric detector. The method is based on the reaction between sulfonamides and p-dimethylaminocinnamaldehyde (p-DAC) in the presence of sodium dodecylsulfate (SDS) in dilute acid medium (hydrochloric acid), with measurement of the reaction products at 565 nm. Experimental design methodology was used to optimize the analytical conditions. The linear range obtained was 10.0-130.0 μg/L, and detection and quantification limits were 3.1 and 10.1 μg/L, respectively. The method was successfully applied to the analysis of sulfonamides in water samples. By coupling the MPFS with the LWCC, the sensitivity was enhanced, reagent consumption was low, and waste generation was minimized. The results obtained with the MPFS method were confirmed by LC-MS.
Keywords: Eco-friendly method; Multi-pumping; Sulfonamides; Water